PATTERNS OF ARTISTIC IMAGE AMONG THE POETS OF ALMAMLOKI ERA - Dr. Mayyadah Abdulqader Imran (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
I discussed in this research the patterns of the artistic image at the poets of ALMAMLOKI era, in terms of visual, auditory, gustatory, olfactory and tactile senses. Which played an important,significant role in drawing their images and emotional experiences are derived from the reality of the situation.Which are mixed with means of forming the rhetorical image that helped poets to translate their reality, to present them in the most beautiful and wonderful image to the recipient.